Teknik Color Correcting untuk Menyiasati Kulit Tidak Merata Anak Muda Masa Kini - Zdihni Zalfa Afrillia; Santi, Nadya Agustina Tiara; Ningrum, Sabila Mutiara; Faiza, Najma Azfa (Jurnal Tata Rias, 2025)
This study explored the application of color correcting techniques to address uneven skin tones commonly experienced by young people today. Data were collected through a qualitative literature review from various credible sources including scientific journals, beauty articles, and expert publications. The analysis focused on the theory of complementary colors in makeup, the selection of concealer shades, application methods, and the psychological impact of using color correcting. The findings reveal that specific concealer colors effectively neutralize skin discolorations such as redness, dark circles, and hyperpigmentation. Moreover, correct application techniques enhance natural skin appearance and boost users’ self-confidence. The technique remains highly relevant in contemporary beauty trends, promoting a natural and healthy look without heavy makeup. Educating young users on color theory and product choice is crucial for optimal results. Additionally, the development of skin-friendly products supports long-term skin health. Color correcting thus serves not only as an aesthetic tool but also as a means of enhancing self-esteem among youth.